Bicatalytic Allylation–Cross-Metathesis Reactions as γ-Carbonyl Cation Equivalents - Henkie, Jake R.; Dhaliwal, Sugadar; Green, James R. (Synlett, 2012)
The products corresponding to the reactions of arenes and γ-carbonyl cations may be obtained by a one-pot, bicatalytic process involving InCl3-catalyzed arene allylation and cross metathesis with electron-deficient alkenes. The process is successful with electronically neutral and electron-rich arenes, and modestly Lewis basic donor groups are tolerated with an increase in InCl3 loading from 10 mol% to 15 mol%, and in one case, 20 mol%.
Keywords: allylation; electrophilic aromatic substitution; indium; metathesis; umpolung